Escherichia ruysiae May Serve as a Reservoir of Antibiotic Resistance Genes across Multiple Settings and Regions - Campos-Madueno, Edgar I.; Aldeia, Claudia; Sendi, Parham; Endimiani, Andrea (Microbiology spectrum, 2023)
Escherichia ruysiae is a recently described species of the cryptic clades III and IV of the genus Escherichia and is commonly found in animals and the environment. This work highlights the zoonotic potential of E. ruysiae , as it has been shown to colonize the human intestinal tract. Gut colonization with multidrug-resistant Enterobacterale s (MDR- Ent ) has reached worrisome levels worldwide. In this context, Escherichia ruysiae is a recently described species mostly found in animals. However, its spread and impact on humans is poorly understood. A stool sample from a healthy individual living in India was screened for the presence of MDR- Ent using culture-based methods. Colonies were routinely identified using matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) and phenotypically characterized by broth microdilution. Illumina and Nanopore whole-genome sequencing (WGS) platforms were implemented to generate a complete assembly. E. ruysiae genomes deposited in international databases were used for a core genome phylogenetic analysis. An extended-spectrum β-lactamase (ESBL)-producing E. coli strain (S1-IND-07-A) was isolated from the stool. WGS confirmed that S1-IND-07-A was indeed E. ruysiae , belonged to sequence type 5792 (ST5792), core genome (cg) ST89059, serotype O13/O129−:H56-like, clade IV phylogroup, and possessed five virulence factors. A copy of bla CTX-M-15 and five other antimicrobial resistance genes (ARGs) were detected in a conjugative IncB/O/K/Z plasmid. A database search identified 70 further E. ruysiae strains from 16 countries (44, 15, and 11 strains isolated from animals, the environment, and humans, respectively). The core genome phylogeny revealed five major STs: ST6467, ST8084, ST2371, ST9287, and ST5792. Three out of the seventy strains possessed important ARGs: OTP1704 ( bla CTX-M-14 ; ST6467), SN1013-18 ( bla CTX-M-15 ; ST5792), and CE1758 ( bla CMY-2 ; ST7531). These strains were of human, environmental, and wild animal origin, respectively. E. ruysiae may acquire clinically important ARGs and transmit them to other species. Due to its zoonotic potential, further efforts are needed to improve routine detection and surveillance across One Health settings. IMPORTANCE Escherichia ruysiae is a recently described species of the cryptic clades III and IV of the genus Escherichia and is commonly found in animals and the environment. This work highlights the zoonotic potential of E. ruysiae , as it has been shown to colonize the human intestinal tract. Importantly, E. ruysiae may be associated with conjugative plasmids carrying clinically relevant antibiotic resistance genes. Therefore, it is important to closely monitor this species. Overall, this study highlights the need for improved identification of Escherichia species and continued surveillance of zoonotic pathogens in One Health settings.